Global Modeling of the Oceanic Source of Organic Aerosols. (27th July 2010) - Myriokefalitakis, Stelios; Vignati, Elisabetta; Tsigaridis, Kostas; Papadimas, Christos; Sciare, Jean; Mihalopoulos, Nikolaos; Facchini, Maria Cristina; Rinaldi, Matteo; Dentener, Frank J.; Ceburnis, Darius; Hatzianastasiou, Nikos; O'Dowd, Colin D.; et al.
Abstract : The global marine organic aerosol budget is investigated by a 3-dimensional chemistry-transport model considering recently proposed parameterisations of the primary marine organic aerosol (POA) and secondary organic aerosol (SOA) formation from the oxidation of marine volatile organic compounds. MODIS and SeaWiFS satellite data of Chlorophyll-a and ECMWF solar incoming radiation, wind speed, and temperature are driving the oceanic emissions in the model. Based on the adopted parameterisations, the SOA and the submicron POA marine sources are evaluated at about 5 Tgyr − 1 (~ 1.5 Tg Cyr − 1 ) and 7 to 8 Tgyr − 1 (~ 4 Tg Cyr − 1 ), respectively. The computed marine SOA originates from the dimethylsulfide oxidation (~ 78%), the potentially formed dialkyl amine salts (~ 21%), and marine hydrocarbon oxidation (~ 0.1%). Comparison of calculations with observations indicates an additional marine source of soluble organic carbon that could be partially encountered by marine POA chemical ageing.